The Effect of Credit Rating, Discretionary Accrual, And Financial Distress on Credit Facilities in Manufacturing Companies in Indonesia - Annisa, Ema; Ningsih, Sri (Universitas Airlangga, 2021)
This study aims to analyze the effect of credit rating, discretionary accrual, and financial distress on credit facilities, namely the rate spread, credit collateral, and maturity date extended by banks. This study uses static panel equations and panel data, consisting of 50 manufacturing companies in Indonesia from 2010 to 2017. The research methods used are the Pooled Least Square (PLS), Fixed Effect Model (FEM), Random Effect Model (REM), and logit panels. This study concludes that earnings management has a negative and insignificant impact on the rate spread and maturity date but positively and significantly affects the collateral variable. Financial distress has a positive and insignificant effect on the rate spread and maturity date but negatively impacts the collateral variable. The company's investment rating has a negative and insignificant impact on the three dependent variables, namely, rate spread, collateral, and maturity date. Keywords: Credit Rating, Discretionary Accrual, Financial Distress, Credit FacilitiesJEL: C23, G21, G24